La protezione dell’infanzia in una prospettiva storica - Bertini, Fabio (Rivista di studi politici internazionali, 2011)
The history of children’s rights is a painful story of pedagogical acquisitions andimprovement of work laws. In the Nineteenth century the children’s destinies are similarto those of women that became the protagonists of important battles for children. Whilepedagogues as Janus Korczak, Ellen Key and Anna Maria Montessori conceive atheory of education, liberty and responsibility, benefactresses such as Kate Courtney,Dorothy Buxton, Mary Sheepshanks, Eglantyne Jebb struggle for childhood’s rights.The International Save the Children Union, the International Red Cross and otherorganisations work together for the International Declaration of the Rights of the Child,proclaimed in 1923. After the second World War, this declaration is the fundamentalbasis on which the United Nations Organisation, in 1946, promotes the birth of Unicef,in the spirit of the San Francisco Charter. Then come the Declaration of the Rights ofthe Child in 1959, and the Convention on the Rights of the Child in 1989. Todayhowever there is a vast world of injuried and denied childhood, which is exposed to thesame work conditions existent at the beginning of this historical path. L’histoire des droits de l’enfant est une histoire difficile de conquêtes pédagogiques etde conquêtes de lois sur le travail. Depuis le XIXèmesiècle, le sort des enfants estparallèle à celui des femmes, qui deviennent protagonistes de la lutte pour les droits del’enfant. Tandis que des pédagogues comme Janus Korczak, Ellen Key et Anna MariaMontessori animent une doctrine de l’éducation, de la liberté et de la responsabilité,des femmes bienfaisantes comme Kate Courtney, Dorothy Buxton, Mary Sheepshanks,Eglantyne Jebb se battent pour les droits de l’enfant. L’Union Internationale de Secoursaux Enfants, la Croix Rouge Internationale et d’autres organisations travaillentensemble pour une Déclaration internationale des droits de l’enfant, proclamée en1923. Après la deuxième guerre mondiale, on bâtit sur cette base la naissance del’Unicef, dans l’esprit de la Charte des Nations Unies, en 1946 à San Francisco. Aprèsviennent la Déclaration des droits de l’enfant en 1959, et la Convention internationalesur les droits de l’enfants en 1989. Cependant, aujourd’hui encore dans une grandepartie du monde entier l’enfance est offensée et niée, exposée aux mêmes conditionsdu début de ce parcours historique.PAROLE CHIAVE: Croce Rossa internazionale; Unicef; Save the Children;Dichiarazione internazionale dei diritti del fanciullo; Convenzione internazionale suidiritti dell’infanzia.